Identifying determinant risk factors for stunting in children under five years of age in Aceh, Indonesia: A structural equation modeling - Azhari, Azhari; Yani, Muhammad; Dimiati, Herlina; Nurjannah, Nurjannah (Acta Biomedica Atenei Parmensis, 2026)
Background and Aim: Stunting is a major public health issue that undermines the quality of human resources. Aceh is a province with diverse community demographics, susceptibility to natural disasters, and a history of social conflict. These conditions complicate health service delivery and contribute to the persistence of stunting. However, the determinants of stunting in Aceh remain insufficiently understood. This study aims to identify effective intervention priorities for reducing stunting in Aceh. Methods: A cross-sectional analysis was conducted using secondary data from the Indonesian Nutritional Status Survey (SSGI) in Aceh Province. The UNICEF conceptual framework guided variable selection. Structural Equation Modeling using Partial Least Squares (SEM-PLS) was applied for multivariate and hypothesis testing. The final dataset comprised 15,865 children under five years of age. Results: SEM analysis identified six statistically significant determinants of stunting (p < 0.001). Birth condition was the most dominant predictor, with the highest t-statistic (t = 10,541). Strong determinants included sick condition (t = 5,887), exclusive breastfeeding (t = 5,074), pregnancy (t = 4,061), and infection (t = 3,873). The model showed an R Square (R² = 0.000 to 0.056) value, and Q Square (Q² = 0.000 to 0.032) that were very low. The Standardized Root Mean Square Residual (SRMR = 0.084) indicated good model fit, while the Goodness of Fit Index (GoF Index = 0.123) showed a low level of fit. Conclusions: Efforts to accelerate stunting reduction in Aceh should emphasize preventing low birth weight, strengthening early and high-quality antenatal care, reducing infectious diseases in children, promoting exclusive breastfeeding, and implementing targeted strategies to reduce stunting.